Discrete Space-Time on the Manifestation of Mass - Austin, Rickey W. (European Scientific Journal, ESJ, 2018)
Schwarzschild’s Metric (Schwarzschild 1916) under specific conditions provides a Taylor series first order discrete length when transforming coordinates between observers. Exploring the consequences of the discrete length produces an a priori result of quantized space-time. Deriving base units from the quantization of space-time and applying elementary charge, exact formulations for the observed Schwarzschild’s discrete units are obtained. These units are equivalent to Planck’s mass, length, time, momentum, force, energy and Planck’s constant (NIST CODATA 2014).